Design and Implementation of a Low-Pressure Briquetting Machine for the Use of Pinus spp. Wood Residues: An Approach to Appropriate Rural Technology - Mario Morales-Máximo; Víctor Manuel Ruíz-García; José Guadalupe Rutiaga-Quiñones; Luis Bernado López-Sosa (Clean Technologies)
This research analyzes the technical feasibility and implementation of an appropriate technology for the production of briquettes from Pinus spp. waste (sawdust and shavings) in a rural community in Michoacán, Mexico. The results indicate that local small-scale briquette production in the Pichátaro community has the potential to boost a local economy based on the manufacturing and marketing of densified solid biofuels. The design of the manual briquetting machine was developed through a participatory approach with community users. Structural simplicity and locally accessible maintenance were prioritized, the aspects that were addressed little in previous studies. The machine allows for the production of briquettes using a low-cost mixture composed of sawdust and Pinus spp. shavings, corn starch, and water. Based on local conditions and production needs, parameters such as reduced processing times and simplified manufacturing methods were identified as essential to establishing an efficient regional production and supply chain. Furthermore, the valorization of solid waste through the production of alternative biofuels contributes to the diversification of the energy matrix in rural residential sectors and small industries in communities in Mexico. The estimated cost of the machine is USD 75.44, and most of its components are easily replaceable, which favors its sustainability and prolonged use. This study demonstrates that the implementation of a low-pressure briquette system based on appropriate rural technologies represents a viable strategy for the use of wood waste and the promotion of sustainable energy solutions in rural communities.